Are biodiversity perception and attitudes context dependent? A comparative study using a mixed-method approach - Bernardo, Fátima (2022)
Urbanization and other human activities have led to habitat destruction and the extinction of a large number of species globally. Despite general acknowledgement that the involvement of citizens in conservation is pivotal to halting the loss of biodiversity, there is still relatively little understanding of the knowledge lay people have of the concept of biodiversity as well as their overall perception of what biodiversity is about. As the majority of the global population is urban or urbanized, this study aims to contribute to the understanding of how the biodiversity value of the place people live in shapes their perceptions, attitudes, preferences, and social representations of biodiversity. Methodologically it engages in a comparative study of two areas in a peri-urban setting, showing a similar composition of artificial and natural land covers. Both areas show the presence of the same range of biodiversity values but a contrasting all-over biodiversity value. A multi-method approach is used combining attitudinal scales, visual methods, and open questions in a questionnaire. The results show that context matters, meaning that experiencing a landscape of higher biodiversity value can shape positively people’s knowledge, perception, and attitudes; and that using mixed methods in a complementary way enhances the understanding of people’s relationship with biodiversity. These results allowed for the conclusion that not only the presence of biodiversity values is relevant, but above all that the promotion and communication of biodiversity values in people’s surroundings through public policies that enhance the social status of biodiversity can contribute to their overall understanding of biodiversity and well as their attitudes. Ultimately, this study shows that novel approaches to green infrastructure planning have to be developed, so as to make biodiversity visible in ways that make it more accessible physically and cognitively.